KARAKTERISTIK KEPRIBADIAN SANTRIWATI SINGLE PARENT DI MA’HAD TAHFIDH AL-QUR’AN PUTRI AL-AMIEN PRENDUAN SUMENEP - Sitti Khotijah; Indah Sukmawati (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2022)
The formation of a perfect child’s personality is a task that is not easy for parents, especially if the parent is a single parent. Some female students at Ma’had Tahfidh Al-Qur'an Putri Al-Amien Prenduan have single parents so they have problems communicating with their surroundings. However, there are also female students who have single parents who have cheerful and friendly personalities. Therefore, this study aims to determine the personality characteristics of female students who are single parents and what are the supporting and inhibiting factors in shaping the personality of female students who are single parents Ma’had Tahfidh Al-Qur'an Putri Al-Amien Prenduan. The research used a qualitative approach with a case study type of research. Data collection techniques used are interviews, observation, and documentation. The results of this study indicate the personality characteristics of female students who are single parents at Ma’had Tahfidh Al-Qur'an Putri Al-Amien Prenduan, namely extroverted personality and introverted personality. Supporting factors in the formation of female students’ personality are internal and external factors, while the inhibiting factors in the formation of female students’ personality are biological factors, upbringing, and tension in the family.